Causal effect of gut microbiota of Defluviitaleaceae on the clinical pathway of “Influenza–Subacute Thyroiditis–Hypothyroidism” - Zhang, Xin; Li, Pei-Heng; Wang, Dongyue; Li, Hancong; Kong, Xiangyu; Zhang, Gongshuang; Zhao, Yue; Liu, Jiaye; Wu, Wenshuang; Zhang, Yuwei; Li, Zhi-Hui; Luo, Han (Frontiers in Microbiology, 2024)
Introduction Hypothyroidism is found affected by gut microbiota. However, it remains unclear which taxon of gut microbiota play a key role in the effect. Further clarifying the key bacteria affects hypothyroidism through what mechanism will be helpful for the prevention of specific clinical pathways towards hypothyroidism. Materials and Methods In Study A, 35 families and 130 genera of gut microbiota are used as exposures, with hypothyroidism as the outcome. The causal effect of the gut microbiota on hypothyroidism is estimated through two-sample Mendelian randomization. Combining results of two taxonomical levels, key taxa are selected, which in Study B are explored investigate their causal association with multiple generally admitted causes of hypothyroidism and their more upstream factors. To further validation and revealing potential mechanism, enrichment analyses of the related genes and interacting transcription factors were performed. Results In Study A, Defluviitaleaceae (OR 0.043, 95%CI 0.005-0.363, p=0.018) / Defluviitaleaceae_UCG_011 (OR 0.385, 95%CI 0.172-0.865, p=0.021) are significantly causally associated with hypothyroidism at both taxonomical levels. In Study B, Defluviitaleaceae family and Defluviitaleaceae_UCG_011 genus show causal association with decreased thyroiditis (Family: OR 0.174, 95%CI 0.046-0.653, p=0.029; Genus: OR 0.139, 95%CI 0.029-0.664, p=0.043), decreased subacute thyroiditis (Family: OR 0.028, 95%CI 0.004-0.213, p=0.007; Genus: OR 0.018, 95%CI 0.002-0.194, p=0.013), decreased influenza (Family: OR 0.818, 95%CI 0.676-0.989, p=0.038; Genus: OR 0.792, 95%CI 0.644-0.974, p=0.027), and increased anti-influenza H3N2 IgG levels (Family: OR 1.934, 95%CI 1.123-3.332, p=0.017; Genus: OR 1.675, 95%CI 0.953-2.943, p=0.073). The enrichment analysis results are consistent with the findings and suggested possible mechanisms. Conclusions Defluviitaleaceae of gut microbiota displays the probability to causally inhibit the clinical pathway of “influenza-Subacute thyroiditis-hypothyroidism”, and the potential as probiotics to prevent from influenza, subacute thyroiditis, and hypothyroidism.